The Art of Co-Creative Media: An Australian Survey - Spurgeon Christina (Cultural Science, 2013)
This article describes how - in the processes of responding to participatory storytelling practices - community, public service, and to a lesser extent, commercial media institutions are themselves negotiated and changed. Although there are significant variations in the conditions, durability, extent, motivations and quality of these developments and their impacts, they nonetheless increase the possibilities and pathways of participatory media culture. This description first frames digital storytelling as a ‘co-creative’ media practice. It then discusses the role of community arts and cultural development (CACD) practitioners and networks as co-creative media intermediaries, and then considers their influence in Australian broadcast and Internet media. It looks at how participatory storytelling methods are evolving in the Australian context and explores some of the implications for cultural inclusion arising from a shared interest in ‘co-creative’ media methods and approaches.